(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: heterotropic pregnancy; ectopic pregnancy; assisted reproductive technique DOI: 10.3329/jcmcta.v21i1.7685 Journal of Chittagong Medical College Teachers’ Association 2010: 21(1):77-79